Klavdij Sluban, immagini in transito - Silvia Mattei (lo Squaderno, 2011)

(untitled)
Three weeks on a cargo ship heading towards Central America, one week on the Trans-Siberian railway from Moscow to Beijing, three days on the Trans-Tibetan railway form Beijing to Lhasa; all around the Baltic Sea and the Black Sea, with countless detours across the Balkan region as well as some photographic “parenthesis” in juvenile correctional centres in the former Yugoslavia, the former Soviet Union, and France. Klavdij Sluban is never in a hurry, he is not a reporter looking for events, rather, a traveller-photographer who abandons himself to the slow pace of creation through discovery. To him, doing photography and travelling are two verbs for the same action and the same existential need: to give a rhythm to the flow of time, to testify one’s presence. His camera establishes the link with the world he crosses through, preferably on foot. Sluban’s photography is one thing with travel, of which it is both the premise and the fruit: images nourish a larger research and ultimately impose a new need to leave. Rare and precious takes are to be assembled into a series only after years of tos and fros in and out the field. His‘reportages’are in fact long-term cycles, now collected in publications such as Balkans Transit (five years); the Caribbean cycle Paradise Lost (four years); Transverses around the Black Sea (ten years); Entre Parenthèses, the photography workshops with juvenile delinquents around the world (fifteen years), East to East on the trains in central Asia (six years).